Tenures and land legislation in British India - Hutton, Henry Dix (Statistical and Social Inquiry Society of Ireland, 1870)
The Irish land question verifies a twofold truth. Every social movement grows out of an antecedent intellectual progress, yet the results of solitary thought gain both in depth and interest by becoming instrumental to the solution of great problems. The impossibility, now recognized, of reforming the relation of landlord and tenant in Ireland by the English system, or economic laissez-faire, has promoted the search after enlarged conceptions in the study of foreign land-systems, and a genuine social philosophy. In this view, and not as suggesting slavish imitation, I invite your attention to the ancient tenures and modern land legislation of British India.
Read Tuesday, 25th January, 1870
Keywords: India; Land legislation; 314.15